2018
DOI: 10.1007/s10971-018-4873-x
|View full text |Cite
|
Sign up to set email alerts
|

Taylor-made aerogels through a freeze-drying process: economic assessment

Abstract: Polymer aerogels reinforced with carbon nanofibers and alumina aerogels reinforced with hydroxyethyl-cellulose have been successfully synthesized by means of a pilot plant freeze-drying process. Their main physicochemical properties have been measured and compared, and their production costs have been computed. The SWOT matrix of the process has been determined from internal and external analyses, revealing the interest of these products as building insulation materials and the need of establishing a detailed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
3
0
1
Order By: Relevance
“…Sensitivity analysis is an economic tool used to identify the main parameters responsible for the cost variations of a project. Different investigations had carried out sensitivity analysis varying the price of fuel, products and raw material, the energy amount required in the process and the cost of operation and maintenance, among others [69][70][71][72][73][74][75]. It was observed that the biomass price variability and the sale price of the products are key parameters on the economic feasibility of a project.…”
Section: Sensitivity Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Sensitivity analysis is an economic tool used to identify the main parameters responsible for the cost variations of a project. Different investigations had carried out sensitivity analysis varying the price of fuel, products and raw material, the energy amount required in the process and the cost of operation and maintenance, among others [69][70][71][72][73][74][75]. It was observed that the biomass price variability and the sale price of the products are key parameters on the economic feasibility of a project.…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…Therefore, in this investigation, a sensitivity analysis was carried out to study the influence of the products price and the biomass prices for combustion and gasification processes. Therefore, the analysis was carried out considering an overestimation and an underestimation of 50% for both parameters (Table 12) [69].…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…Para tanto, serão mostrados os passos necessários para a construção, assim como os resultados obtidos a partir de uma planilha eletrônica empregada como ferramenta de ensino-aprendizagem, a qual pode ser desenvolvida utilizando softwares como Microsoft Excel ou LibreOffice Calc, ampliando assim o horizonte de aprendizagem e complementando esta atividade de importância para disciplinas de Química Geral, Balanço de Massa, Análise de Alimentos e práticas de laboratórios para a Engenharia (CABEZA et al, 2016;SIMÓN-HERRERO et al, 2019) this program could simulate the dynamic concentration profiles inside the column, being a useful teaching tool. The model comprises non-stationary mass balances for recovered compounds in both phases (solid and supercritical CO2.…”
Section: Introductionunclassified
“…Since it was first synthesized, carbon aerogel has attracted significant attention for potential insulation applications, and in particular high temperature insulation, due to the material's extraordinarily high temperature resistance; carbon aerogel retains its low thermal conductivity up to 2800°C [60]. To date, the commercialization of carbon aerogel remains limited [61], and little consideration has been given to it as a potential building insulation material, likely due to its large manufacturing cost and low mechanical strength [62]. Nonetheless, as with many carbon-based "super materials", enthusiasm remains for the applications of carbon aerogel.…”
Section: Carbon Aerogelmentioning
confidence: 99%